2016
DOI: 10.4254/wjh.v8.i29.1205
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation in cirrhosis: Emphasis on the phase angle

Abstract: Protein-calorie malnutrition (PCM) is a common condition in cirrhotic patients, leading to a worse prognosis, complications, poor quality of life and lower survival rates. Among ways of assessing nutritional status, there are anthropometric methods such as the evaluation of the triceps skinfold, the arm circumference, the arm muscle circumference and the body mass index, and non-anthropometric methods such as the subjective global assessment, the handgrip strength of non-dominant hand, and the bioelectrical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 56 publications
8
28
0
Order By: Relevance
“…In agreement with a previous study, we found that cirrhosis and malnourishment were associated with low PhA, which has been considered a predictor of poor survival in patients with chronic liver disease . Importantly, this is the first study to demonstrate an association between low PhA and low FFM in patients with CHC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with a previous study, we found that cirrhosis and malnourishment were associated with low PhA, which has been considered a predictor of poor survival in patients with chronic liver disease . Importantly, this is the first study to demonstrate an association between low PhA and low FFM in patients with CHC.…”
Section: Discussionsupporting
confidence: 93%
“…Phase angle (PhA) is another nutrition BIA-derived measurement that has also been used in the management of patients with chronic liver diseases. 13 Particularly in cirrhotic patients, a low level of PhA has been found to be a predictor of poor survival. 13 The pathogenesis of MM loss in patients with CHC is multifactorial and not fully understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the limitations of BIA, the clinically established bioelectrical impedance parameter is the phase angle [41]. BIA is represented by the vector Z, which is a combination of the perpendicular vectors R and Xc.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, R is associated with hydration, whereas Xc reflects cellularity and cells integrity. The PA data correlated significantly with the presence of malnutrition and with the stage of liver disease, indicating that it might be considered a good prognostic marker in patients with cirrhosis, with and without edema and/or ascites [30]. This information appears clinically relevant and it should be confirmed by larger clinical trials during long term follow-up.…”
Section: Nutritional Assessment In Cirrhosismentioning
confidence: 99%